Microcrystal / amorphous halide solid electrolyte and preparation method and application thereof

By co-doping two cations and anions in the lithium zirconium halide solid electrolyte and preparing the microcrystalline/amorphous structure through high-energy ball milling method, the problem of low ion conductivity of the lithium zirconium halide solid electrolyte is solved, achieving efficient conductivity improvement and excellent battery performance.

CN119873893AActive Publication Date: 2025-04-25CHINA UNIV OF MINING & TECH (BEIJING)

Patent Information

Application Number
CN202510059039.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-25
Estimated Expiration
2045-01-15

AI Technical Summary

Technical Problem

The room temperature ionic conductivity of existing lithium zirconium halide solid electrolytes is relatively low, which limits its application.

Method used

Two cations and anions are used to co-dopize the modified lithium zirconium halide, the specific chemical formula is LixZr1-y-zTayM1zXuOδ, where M1 is Nb, Hf, Mo, W, X is Cl, Br, I, 1.4≤x≤4, 0.3≤y≤0.7, 0.1≤z≤0.2, 4

Benefits of technology

The room temperature ionic conductivity of lithium zirconium halide solid electrolyte is significantly improved to reach more than 2.5mS/cm, and supports the normal charging and discharging of the battery at -20℃, improving the rate performance and discharge specific capacity of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119873893A_ABST
    Figure CN119873893A_ABST
Patent Text Reader

Abstract

The invention relates to a microcrystal / amorphous halide solid electrolyte which is doped and modified lithium zirconium halide, and the chemical formula of the microcrystal / amorphous halide solid electrolyte is Li < x > Zr < 1-y-z > Ta < y > M < 1z > X O < delta >, in the formula, M1 is any one of Nb, Hf, Mo and W, X is at least one of Cl, Br and I, 1.4 < = x < = 4, 0.3 < = y < = 0.7, 0.1 < = z < = 0.2, 4 < u < = 5, 0.7 < = delta < = 2. According to the invention, due to the synergistic effect of two high-valence positive ions and negative ion O < 2-> doping, lithium ions are easier to migrate in crystal lattices, the migration distance is reduced, and the original lithium zirconium-based halide with a trigonal structure is converted into an amorphous structure mixed with a small amount of microcrystals, so that the improvement of the ionic conductivity of the lithium zirconium-based halide is realized; the room-temperature ionic conductivity of the finally prepared microcrystal / amorphous halide solid electrolyte is 2.5 mS / cm or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid-state batteries, and in particular relates to a microcrystalline / amorphous halide solid electrolyte and a preparation method and application thereof. Background Art

[0002] As the next generation of energy storage technology, all-solid-state batteries are expected to solve the safety issues of commercial lithium-ion batteries and further improve their energy density. As the core of all-solid-state batteries, the performance of solid electrolytes directly affects the electrochemical performance of all-solid-state batteries. Amorphous solid electrolytes have good flexibility, are easy to manufacture, and have isotropic ionic conductivity; but their conductivity off the ground is usually low. Crystalline solid electrolytes with long-range ordered structures exhibit continuous and rapid lithium ion conduction capabilities, but have low oxidation stability and poor interfacial compatibility with negative electrodes (lithium metal) and positive electrode materials (lithium iron phosphate, lithium cobalt oxide). If the advantages of the two solid electrolytes can be combined, it will be a good strategy for preparing high-performance solid electrolytes. Among the common crystalline solid electrolytes, lithium zirconium chloride Li2ZrCl6 has attracted much attention due to its low price and high oxidation resistance; however, its room temperature ionic conductivity of less than 1mS / cm limits its application. Therefore, it is of great significance to improve the ionic conductivity of lithium zirconium halides.

[0003] In order to effectively improve the ionic conductivity of zirconium-based halide electrolytes, heterovalent cation doping strategies are widely used. In the prior art, heterovalent cations with a valence lower than +4 are generally used for doping, because cations with a valence higher than +4 replace Zr 4+ This will cause the lithium concentration in the lattice to be adjusted to a low concentration, which will be detrimental to the electrochemical performance. Tian et al. (J. Energy Chem. 79 (2023) 348-356) reported that by using appropriate Mg 2+ and Zn 2+ Heterovalent doping of Li2ZrCl6 can effectively improve ionic conductivity, where Li 2.1 Zr 0.95 Mg 0.05 Cl6 can show 0.62mS / cm. Similarly, Jung et al. (Adv.Energy Mater.11(2021)2003190) used Fe 3+ The element was doped to modify the zirconium-based halide and effectively increased the ionic conductivity from 0.4mS / cm to 0.98mS / cm. Xie et al. (Chin.Chem.Lett.33(2022)4635-4639) successfully doped In 3+ Doped into the Li2ZrCl6 crystal structure, and the maximum ionic conductivity (1.08mS / cm) was obtained when the doping ratio was 0.25. 4+, the research on high-valent cation doping is relatively small. In addition, the anion F -1 Doped modified zirconium-based halide electrolytes have also been studied, but they are still unsatisfactory due to low ionic conductivity. Summary of the invention

[0004] In view of the problem of low room temperature ionic conductivity of solid electrolytes in the prior art, the present invention provides a microcrystalline / amorphous halide solid electrolyte and a preparation method thereof to solve the above problem.

[0005] The present invention adopts the following technical solutions to achieve the above purpose:

[0006] A microcrystalline / amorphous halide solid electrolyte, which is a doped modified lithium zirconium halide, and its chemical formula is Li x Zr 1-y- z Ta y M1 z X u O δ ; Wherein, M1 is any one of Nb, Hf, Mo, and W, X is at least one of Cl, Br, and I, 1.4≤x≤4, 0.3≤y≤0.7, 0.1≤z≤0.2, 4<u≤5, and 0.7≤δ≤2.

[0007] Preferably, M1 is Nb or Hf; and X is Cl.

[0008] Preferably, 2.4≤x≤3.2, 0.3≤y≤0.5, and 1.2≤δ≤1.6.

[0009] In a preferred technical solution of the present invention, the microcrystalline / amorphous halide solid electrolyte is Li 3.2 Zr 0.4 Ta 0.5 Nb 0.1 Cl 4.6 O 1.6 .

[0010] Furthermore, the mass fraction of the microcrystalline part in the microcrystalline / amorphous halide solid electrolyte is 5% to 10%.

[0011] Furthermore, the grain size of the microcrystalline part in the microcrystalline / amorphous halide solid electrolyte is 10 nm to 200 nm.

[0012] The present invention also provides a method for preparing the above-mentioned microcrystalline / amorphous halide solid electrolyte, which is a high-energy ball milling method, comprising the following steps:

[0013] (S1) Press Li x Zr 1-y-z Ta y M1 z Xu O δ A certain amount of lithium source, zirconium source, tantalum source and M1 source are mixed in a stoichiometric ratio to obtain a mixture;

[0014] (S2) placing the mixture and the grinding balls in a ball mill, and subjecting the mixture to high-energy ball milling under an inert atmosphere to obtain Li x Zr 1-y-z Ta y M1 z X u O δ Microcrystalline / amorphous halide solid electrolytes.

[0015] Furthermore, in step (S1), the lithium source is lithium oxide or lithium halide; the zirconium source is zirconium halide; the tantalum source is tantalum halide; and the M1 source is a halide of M1.

[0016] Furthermore, in step (S1), the mixing is performed by manual grinding for 5 to 20 minutes.

[0017] Furthermore, in step (S2), the grinding balls are zirconium oxide grinding balls with a diameter of 4 to 8 mm; the mass ratio of the mixture to the grinding balls is 1:(10 to 30), preferably 1:(20 to 30); the inert atmosphere is nitrogen and / or argon; the conditions for the high-energy ball milling treatment are: the ball mill rotation speed is 300 to 800 rpm; and the ball milling time is 12 to 36 hours.

[0018] Furthermore, after high-energy ball milling, step (S2) further includes: annealing the material after high-energy ball milling in an inert atmosphere, and the annealing conditions are: temperature 100-200° C., time 2-5 hours.

[0019] The present invention also provides the application of the aforementioned microcrystalline / amorphous halide solid electrolyte in an all-solid-state lithium battery.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] (1) In the present invention, two cations and anions are co-doped to modify lithium zirconium halide, the anion is O 2- , one of the two cations is Ta 5+ , the other is Hf 4+ , Nb 5+ 、Mo 5+ or W 6+The valence states of the two cations used as dopants in the present invention are both higher than or equal to +4. The high-valence cations have stronger binding energy with the anions with high electronegativity, which weakens the binding energy between lithium ions and anions, which is conducive to better migration of lithium ions in the crystal lattice. The high-valence cations selected in the present invention have smaller ionic radius. When doped in the zirconium-based halide crystal structure, they can reduce the migration distance of lithium ions and thus improve the ionic conductivity of the material. In addition, under normal circumstances, cations with a valence state higher than +4 replace Zr 4+ The lithium in the lattice will be adjusted to a low concentration, but the inventor unexpectedly found that the anion O 2- Doping will not adjust the lithium in the lattice to a low concentration. 2- The synergistic effect of doping makes it easier for lithium ions to migrate in the lattice, the migration distance is reduced, and the lithium concentration in the lattice is not reduced, thereby achieving an improvement in its ionic conductivity. 2- The co-doping of 200 Å and 250 Å transforms the original tripartite structure of lithium zirconium-based halide into an amorphous structure with a small amount of microcrystals, which reduces the crystallinity and further improves the ionic conductivity of the material. The final chemical formula is Li x Zr 1-y-z Ta y M1 z X u O δ The room temperature ionic conductivity of the microcrystalline-amorphous halide solid electrolyte is above 2.5 mS / cm.

[0022] (2) The room temperature ionic conductivity of the microcrystalline-amorphous halide solid electrolyte of the present invention is significantly improved, and the metal lithium battery assembled with the existing 4V-level positive electrode material shows higher discharge specific capacity and excellent rate performance; at the same time, the solid electrolyte supports the normal charging and discharging of the battery at -20°C. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The XRD spectra of the solid electrolytes prepared in Examples 1-3 and Comparative Example 1 are shown.

[0024] Figure 2 The solid electrolyte Li prepared in Example 1 3.2 Zr 0.4 Ta 0.5 Nb 0.1 Cl 4.6 O 1.6 Discharge curves of the assembled battery at different rates at room temperature and -20°C, where Figure 2(a) is the discharge curve at different rates at room temperature, and (b) is the discharge curve at different rates at -20°C.

[0025] Figure 3 The discharge curves of the battery assembled with solid electrolyte prepared in Comparative Example 1 at different rates at room temperature and -20°C are as follows: Figure 3 (a) is the discharge curve at different rates at room temperature, and 3(b) is the discharge curve at different rates at -20°C. DETAILED DESCRIPTION

[0026] The present invention will be further described below in conjunction with specific examples, but the present invention is not limited to the following examples.

[0027] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.

[0028] Example 1 - Preparation of microcrystalline / amorphous halide solid electrolyte Li 3.2 Zr 0.4 Ta 0.5 Nb 0.1 Cl 4.6 O 1.6 (x=3.2, y=0.5, z=0.1, u=4.6, δ=1.6)

[0029] (S1) Press Li 3.2 Zr 0.4 Ta 0.5 Nb 0.1 Cl 4.6 O 1.6 Corresponding to the stoichiometric ratio of each element, a certain amount of Li2O, ZrCl4, TaCl5 and NbCl5 were put into a mortar and manually ground for 10 min to obtain a mixture;

[0030] (S2) The mixture and grinding zirconium balls with a diameter of 5 mm were placed in a ball mill at a mass ratio of 1:25, and high-energy ball milling was performed in a planetary ball mill under nitrogen protection. The ball mill speed was 500 rpm, and forward and reverse ball milling were performed alternately. After forward ball milling for 15 minutes, reverse ball milling was performed for 15 minutes. This cycle was repeated and the total ball milling time was controlled to be 24 hours. After the ball milling was completed, the chemical formula of Li 3.2 Zr 0.4 Ta 0.5 Nb 0.1 Cl 4.6 O 1.6 Microcrystalline / amorphous halide solid electrolytes.

[0031] Example 2---Preparation of microcrystalline / amorphous halide solid electrolyte Li 1.4 Zr0.6 Ta 0.3 Nb 0.1 Cl 4.4 O 0.7

[0032] The rest is the same as Example 1, except that the ratios of Li, Zr, Ta, M1 (Nb), and X (Cl) in the chemical formula are different, x = 1.4, y = 0.3, z = 0.1, u = 4.4, δ = 0.7, and the final chemical formula is Li 1.4 Zr 0.6 Ta 0.3 Nb 0.1 Cl 4.4 O 0.7 Microcrystalline / amorphous halide solid electrolytes.

[0033] Example 3 - Preparation of microcrystalline / amorphous halide solid electrolyte Li 2.4 Zr 0.5 Ta 0.3 Nb 0.2 Cl 4.5 O 1.2

[0034] The rest is the same as Example 1, except that the ratios of Li, Zr, Ta, M1 (Nb), and X (Cl) in the chemical formula are different, x = 2.4, y = 0.3, z = 0.2, u = 4.5, δ = 1.2, and the final chemical formula is Li 2.4 Zr 0.5 Ta 0.3 Nb 0.2 Cl 4.5 O 1.2 Microcrystalline / amorphous halide solid electrolytes.

[0035] Example 4 - Preparation of microcrystalline / amorphous halide solid electrolyte Li 3.2 Zr 0.3 Ta 0.5 Nb 0.2 Cl 4.7 O 1.6

[0036] The rest is the same as Example 1, except that the ratios of Li, Zr, Ta, M1 (Nb), and X (Cl) in the chemical formula are different, x = 3.2, y = 0.5, z = 0.2, u = 4.7, δ = 1.6, and the final chemical formula is Li 3.2 Zr 0.3 Ta 0.5 Nb 0.2 Cl 4.7 O 1.6 Microcrystalline / amorphous halide solid electrolytes.

[0037] Example 5 - Preparation of microcrystalline / amorphous halide solid electrolyte Li4Zr 0.1 Ta 0.7 Nb 0.2 Cl 4.9 O2

[0038] The rest is the same as Example 1, except that the ratios of Li, Zr, M1(Nb), and X(Cl) in the chemical formula are different, x=4, y=0.7, z=0.2, u=4.9, δ=2, and the final chemical formula is Li4Zr 0.1 Ta 0.7 Nb 0.2 Cl 4.9 Microcrystalline / amorphous halide solid electrolytes for O2.

[0039] Example 6 - Preparation of microcrystalline / amorphous halide solid electrolyte Li 3.2 Zr 0.4 Ta 0.5 Hf 0.1 Cl 4.5 O 1.6

[0040] The rest is the same as Example 1, except that the type of M1 in the chemical formula is different, M1 is Hf; accordingly, HfCl4 is used instead of NbCl5 in step (S1), and the final product is Li 3.2 Zr 0.4 Ta 0.5 Hf 0.1 Cl 4.5 O 1.6 Microcrystalline / amorphous halide solid electrolytes.

[0041] Example 7 - Preparation of microcrystalline / amorphous halide solid electrolyte Li 3.2 Zr 0.4 Ta 0.5 Mo 0.1 Cl 4.6 O 1.6

[0042] The rest is the same as Example 1, except that the type of M1 in the chemical formula is different. M1 is Mo, and accordingly, MoCl5 is used in step (S1) instead of NbCl5, and finally a chemical formula of Li 3.2 Zr 0.4 Ta 0.5 Mo 0.1 Cl 4.6 O 1.6 Microcrystalline / amorphous halide solid electrolytes.

[0043] Example 8 - Preparation of microcrystalline / amorphous halide solid electrolyte Li3.2 Zr 0.4 Ta 0.5 W 0.1 Br 4.7 O 1.6

[0044] The rest is the same as Example 1, except that the types of M1 and X in the chemical formula are different, M1 is W, X is Br, and accordingly, ZrBr4 is used instead of ZrCl4 in step (S1), and TaBr5 is used instead of TaCl 5, Using WBr6 to replace NbCl5, the final product is Li 3.2 Zr 0.4 Ta 0.5 W 0.1 Br 4.7 O 1.6 Microcrystalline / amorphous halide solid electrolytes.

[0045] Comparative Example 1

[0046] The rest is the same as Example 1. In step (S1), a certain amount of LiCl and ZrCl4 are put into a mortar and manually ground for 10 minutes according to the stoichiometric ratio of each element corresponding to the chemical formula Li2ZrCl6 to obtain a mixture; step (S2) is the same as Example 1, and a solid electrolyte with a chemical formula of Li2ZrCl6 is obtained.

[0047] Comparative Example 2

[0048] The rest is the same as Example 1, except that Zn is used instead of Ta, that is, ZnCl2 is used instead of TaCl5 in step (S1), and finally a product with the chemical formula Li 3.2 Zr 0.4 Zn 0.5 Nb 0.1 Cl 3.1 O 1.6 of solid electrolytes.

[0049] Comparative Example 3

[0050] The rest is the same as Example 1, except that there is no Nb in the chemical formula. Accordingly, in step (S1), the chemical formula Li 3.2 Zr 0.5 Ta 0.5 Cl 7.7 A certain amount of LiCl, ZrCl4, and TaCl5 were put into a mortar and manually ground for 10 minutes to obtain a mixture; the final product was Li 3.2 Zr 0.5 Ta 0.5 Cl 7.7 of solid electrolytes.

[0051] Testing and analysis

[0052] 1. Structural performance

[0053] The solid electrolytes prepared in the examples and comparative examples were subjected to X-ray diffraction tests. The XRD spectra of the solid electrolytes prepared in Examples 1-3 and Comparative Example 1 are as follows: Figure 1 As shown in the figure, comparative example 1 shows an obvious tripartite structure (hcp), and the space group is In Example 1-3, by co-doping two cations and anions, the original diffraction peak of the tripartite structure basically disappeared and no new strong diffraction peak appeared, but the characteristics of the amorphous structure were shown. o and 35 o There are weak diffraction peaks on the left and right to varying degrees. By comparing with the PDF standard card, this is the diffraction peak of LiCl microcrystals. Similarly, at 32 o There are also weak diffraction peaks on the left and right, which are the diffraction peaks of Li2O microcrystals, indicating that the anion-cation co-doping strategy of the present invention can transform the original hcp structure Li2ZrCl6 material into an amorphous structure, and the amorphous structure is mixed with trace amounts of LiCl and Li2O crystals. The mass fraction of microcrystals in Examples 1-3 is calculated to be between 5% and 10% by the external standard method. This halide electrolyte with a special structure may improve its electrochemical performance.

[0054] 2. Electrochemical Performance

[0055] (1) Conductivity test: The solid electrolytes prepared in the examples and comparative examples were tested for conductivity. The method was as follows: in an environment with a water content of less than 50 ppm, 60 mg of the solid electrolyte powder was accurately weighed and placed in a solid electrolyte test mold, and a pressure of 250 MPa was applied externally for tableting. Electrochemical impedance spectroscopy was performed by cold pressing based on an electrochemical workstation. The test results are shown in Table 1.

[0056] Table 1 Conductivity test

[0057]

[0058]

[0059] It can be seen from Table 1 that the prepared microcrystalline / amorphous halide solid electrolyte Li x Zr 1-y- z Ta y M1 z X u O δThe room temperature ionic conductivity of the samples was significantly higher than that of the control samples, both being above 2.5 mS / cm.

[0060] (2) Rate performance test: The solid electrolytes prepared in the embodiments and comparative examples are used in lithium batteries, and the assembly process is as follows: in an environment with a water content of less than 50 ppm, first accurately weigh 60 mg of solid electrolyte and load it into a solid battery mold with a diameter of 10 mm, press it at a pressure of 1 ton for 2 minutes, then evenly spread 5 mg of composite positive electrode on one side of the solid electrolyte, and press it at a pressure of 2 tons for 2 minutes, wherein the composite positive electrode material is obtained by uniformly mixing single crystal NCM811 and solid electrolyte in a mass ratio of 7:3. Invert the above-mentioned solid battery mold, spread a layer of 40 mg of Li6PS5Cl electrolyte on the other side of the solid electrolyte, and press it at a pressure of 2 tons for 10 minutes. Finally, indium foil and lithium foil with a diameter of 10 mm and a thickness of 100 μm and 30 μm, respectively, are attached to one side of the Li6PS5Cl electrolyte, and pressed at a pressure of 0.5 tons. The prepared battery is subjected to rate performance test under a pressure of 100 MPa, and the charge and discharge voltage range is 2.3-3.7 V vs. Li + / LiIn.

[0061] The solid electrolyte Li prepared in Example 1 3.2 Zr 0.4 Ta 0.5 Nb 0.1 Cl 4.6 O 1.6 The discharge curves of the assembled battery at different rates at room temperature and -20°C are shown in Figure 2. Figure 2 As shown, Figure 2 (a) is the discharge curve at different rates at room temperature. Figure 2 (b) is the discharge curve at different rates at -20°C. The discharge curves of the battery assembled with solid electrolyte prepared in Comparative Example 1 at different rates at room temperature and -20°C are shown in FIG. Figure 3 As shown, Figure 3 (a) is the discharge curve at different rates at room temperature. Figure 3 (b) is the discharge curve at different rates at -20℃.

[0062] The discharge gram capacities of various embodiments and comparative examples at different rates at room temperature and -20°C are shown in Table 2.

[0063] Table 2 Discharge capacity in grams at different rates

[0064]

[0065] As can be seen from Table 2, the chemical formula prepared by the embodiment is Li x Zr 1-y-z Ta yM1 z X u O δ The solid-state mold battery assembled with microcrystalline-amorphous halide solid electrolyte shows higher discharge specific capacity and excellent rate performance; at the same time, the solid electrolyte supports normal charging and discharging of the battery at -20°C.

[0066] The above specific implementations are only illustrative of the content of the present invention and do not represent limitations of the content of the present invention. Those skilled in the art can imagine that the specific structure of the present invention may have other variations.

Claims

1. A microcrystalline / amorphous halide solid electrolyte, which is a doped and modified lithium zirconium halide, characterized in that: Its chemical formula is Li x Zr 1-y-z Ta y M1 z X u O δ ; Wherein, M1 is any one of Nb, Hf, Mo, and W, X is at least one of Cl, Br, and I, 1.4≤x≤4, 0.3≤y≤0.7, 0.1≤z≤0.2, 4<u≤5, and 0.7≤δ≤2.

2. The microcrystalline / amorphous halide solid electrolyte according to claim 1, characterized in that: M1 is Nb or Hf; X is Cl.

3. The microcrystalline / amorphous halide solid electrolyte according to claim 1, characterized in that: 2.4≤x≤3.2, 0.3≤y≤0.5, 1.2≤δ≤1.

6.

4. The microcrystalline / amorphous halide solid electrolyte according to claim 1, characterized in that: The microcrystalline / amorphous halide solid electrolyte is Li 3.2 Zr 0.4 Ta 0.5 Nb 0.1 Cl 4.6 O 1.6 .

5. The microcrystalline / amorphous halide solid electrolyte according to claim 1, characterized in that: The mass fraction of the microcrystalline part in the microcrystalline / amorphous halide solid electrolyte is 5% to 10%.

6. The microcrystalline / amorphous halide solid electrolyte according to claim 1, characterized in that: The grain size of the microcrystalline part in the microcrystalline / amorphous halide solid electrolyte is 10nm to 200nm.

7. The method for preparing the microcrystalline / amorphous halide solid electrolyte according to any one of claims 1 to 6, characterized in that: It is a high energy ball milling method, comprising the following steps: (S1) Press Li x Zr 1-y-z Ta y M1 z X u O δ A certain amount of lithium source, zirconium source, M1 source and M2 source are mixed in a stoichiometric ratio to obtain a mixture; (S2) placing the mixture and the grinding balls in a ball mill, and subjecting the mixture to high-energy ball milling under an inert atmosphere to obtain Li x Zr 1-y-z Ta y M1 z X u O δ Microcrystalline / amorphous halide solid electrolytes.

8. The preparation method according to claim 1, characterized in that: In step (S1), the lithium source is lithium oxide or lithium halide; the zirconium source is zirconium halide; the tantalum source is tantalum halide; and the M1 source is a halide of M1.

9. The preparation method according to claim 1, characterized in that: In step (S1), the mixing is performed by manual grinding for 5 to 20 minutes; and / or In step (S2), the grinding balls are zirconium oxide grinding balls with a diameter of 4 to 8 mm; the mass ratio of the mixture to the grinding balls is 1:(10 to 30), preferably 1:(20 to 30); the inert atmosphere is nitrogen and / or argon; the conditions for the high-energy ball milling treatment are: the ball mill rotation speed is 300 to 800 rpm; and the ball milling time is 12 to 36 hours.

10. Use of the microcrystalline / amorphous halide solid electrolyte according to any one of claims 1 to 6 in an all-solid-state lithium battery.

Citation Information

Patent Citations

  • Solid electrolyte material and application thereof

    CN114614081A

  • Halide solid electrolyte and preparation method and application thereof

    CN117410553A

  • Halide type electrolyte material, preparation method thereof and lithium secondary battery

    CN118281303A

  • Chlorine oxide solid electrolyte as well as preparation method and application thereof

    CN118712468A

  • Oxidation halide solid electrolyte and preparation method and application thereof

    CN118748268A

Cited By

  • All-solid-state lithium ion battery containing oxyhalide composite solid electrolyte

    CN120511352A